Perceptions about participation in a 12-week walking program for people with severe knee osteoarthritis: a qualitative analysis. Issue 7 (27th March 2019) - Wallis, Jason A.; Webster, Kate E.; Levinger, Pazit; Singh, Parminder J.; Fong, Chris; Taylor, Nicholas F.
Abstract: Purpose: To explore the perceptions of people with severe knee osteoarthritis and increased cardiovascular risk about participating in a walking program. Methods: Qualitative study using semistructured interviews for people with severe knee osteoarthritis and increased cardiovascular risk who participated in a 12-week walking program. Interviews were audiotaped, transcribed verbatim, member-checked, coded and themes developed using thematic analysis. Findings were triangulated with quantitative data including pain, function and cardiovascular risk factors from previously reported data. Results: Twenty-one participants were interviewed after the completion of the walking program. The main theme identified was the preoccupation with the knee including pain, damage and the view that surgery was required. Three subthemes to emerge were (i) the perception of functional, cardiovascular and psychosocial benefits with the walking program; (ii) that supervision, monitoring and commitment were important enablers; and (iii) external factors such as ill-health, weather and the environment were key barriers. The perceived functional and cardiovascular benefits converged with results from quantitative data. Conclusions: Even when patients with severe osteoarthritis of the knee report other benefits from participating in a walking program, the core theme to emerge was their preoccupation with knee pain, knee damage and the view that they needed a knee replacement. Implications for Rehabilitation: Patients with severe osteoarthritis of the knee and moderate cardiovascular risk reported functional, cardiovascular and psychosocial benefits from participating in a walking program. Despite patients reporting functional, cardiovascular and psychosocial benefits, the core theme to emerge was their preoccupation with knee pain, knee damage and the view that they needed a knee replacement. The core theme highlights the challenges in promoting physical activity for patients with severe knee osteoarthritis.